O efeito da síncope nas proparoxítonas: análise fonológica e variacionista com dados do sudoeste goiano - Lima, Giselly de Oliveira (2008)
In this dissertation a very common phenomenon in the Brazilian Portuguese, and, more specifically in the Portuguese spoken in the southwest part of the state of Goiás has been studied: the syncope of the medial post-stressed vowel in antepenultimate stressed words (pétala > pét[Ø]la> pétla). In order to analyze the effects of the syncope in antepenultimate stressed words, which is the main objective of this work, two theoretical models from the Metrical Phonology were adopted: one for the treatment of the syllable proposed by Selkirk (1982) and another about the main stress as proposed by Hayes (1995). Such analysis, based on these theoretical models, has proven that the syncope triggers three phonological processes: assimilation, resyllabification and foot restructuring. This way, because of the resyllabification process, the consonantal segment of the post-stressed syllable is either incorporated to the coda of the stressed syllable or to the onset of the final unstressed syllable. This process causes the foot restructuring therefore turning antepenultimate stressed words into penultimate stressed words. In the assimilation process a segment can assimilate characteristics of a precedent segment cócega > cóska (progressive assimilation) or assimilate characteristics of the following segment físico > físco (regressive assimilation). However, the phenomenon under investigation also this research to an analysis that follows the guidelines of Sociolinguistics. Under the guidance of the Variation Theory, the linguistic and extra-linguistic variables that favor the syncope were statistically analyzed. The results were obtained through the use of the statistical analysis program GOLDVARB (Windows). The program has shown that the main group of factors that favored the syncope in the southwest part of the state of Goiás are: educational rate, the following phonological context, the preceding phonological context, the articulatory features of the vowel, the weight of the stressed syllable, geographic region and gender.